PROTOTYPE MONITORING ARUS DAN TEGANGAN MENGGUNAKAN SMS GATEWAY - Adam Adam; Hikmatul Amri (Universitas Muhammadiyah Ponorogo, 2019)
Digitalization affects the development of electricity usage monitoring systems for home appliances. But there are still many users of electricity who have not been able to monitor electric power in detail. This study discusses the prototype of an electric scale monitoring system such as current and voltage. This prototype utilizes AC SCT 013-000 current sensor and ZMPT101B voltage sensor to read electrical quantities. Arduiono Mega processes data generated by sensors. This monitoring system sends data using an 800L SIM to Mobile via SMS. Voltage and electric current data is also stored in the data logger. The SIM800L module test shows a success rate of 80%.